Resistensi Aedes aegypti Terhadap Insektisida: Studi pada Insektisida Rumah Tangga - Suri Dwi Lesmana; Esy Maryanti; Lilly Haslinda; Afiata Jazila; Mislindawati Mislindawati (Jurnal Ilmu Kedokteran, 2021)
Dengue hemorrhagic fever is a public health problem in Pekanbaru. It is transmitted by Aedes aegypti mosquitoes. The use of insecticides to kill vectors is a common practice. It is often used in outbreaks by fogging and daily use of insecticides in households. Household insecticides contain a variety of active ingredients such as organophosphates, carbamates, synthetic pyrethroids, and their combinations. This study aims to determine the sensitivity of Ae. aegypti mosquitoes from various household insecticides. This research was descriptive research by conducting a susceptibility test from World Health Organization. Adult mosquitoes were obtained from the breeding of larvae collected from dengue-endemic areas in Pekanbaru. Three types of insecticides are widely distributed in the market consisting of insecticides X with the active ingredient cypermethrin, transfluthrin, and imiprothrin, insecticide Y containing transfluthrin, and insecticide Z containing pralethrin and sifluthrin. Each insecticide was exposed to an adult mosquito by applying insecticides to filter paper and exposed for 1 hour and observed after 24 hours. The death of mosquitoes in the three types of insecticides is less than 80%. Based on the WHO criteria mortality of less than 80% showed a resistant mosquito. This tendency of resistance is probably caused by long-term continuous use.